Across the barricades - Neville, David Ian; Lingard, Joan. (Oxford Oxford University Press, 1990)
Relates the present-day struggle in Ireland as it affects the developing relationship between Sadie, a Protestant, and Kevin, a Catholic.
Original novel published by Hamish Hamilton 1972.
Keywords: Ireland -- Fiction